The Genome of Nitrospina gracilis Illuminates the Metabolism and Evolution of the Major Marine Nitrite Oxidizer - Luecker, Sebastian; Nowka, Boris; Rattei, Thomas; Spieck, Eva; Daims, Holger (Frontiers in Microbiology, 2013)
In marine systems, nitrate is the major reservoir of inorganic fixed nitrogen. The only known biological nitrate-forming reaction is nitrite oxidation, but despite its importance, our knowledge of the organisms catalyzing this key process in the marine N-cycle is very limited. The most frequently encountered marine NOB are related to Nitrospina gracilis, an aerobic chemolithoautotrophic bacterium isolated from ocean surface waters. To date, limited physiological and genomic data for this organism were available and its phylogenetic affiliation was uncertain. In this study, the draft genome sequence of Nitrospina gracilis strain 3/211 was obtained. Unexpectedly for an aerobic organism, N. gracilis lacks classical reactive oxygen defense mechanisms and uses the reductive tricarboxylic acid cycle for carbon fixation. These features indicate microaerophilic ancestry and are consistent with the presence of Nitrospina in marine oxygen minimum zones. Fixed carbon is stored intracellularly as glycogen, but genes for utilizing external organic carbon sources were not identified. N. gracilis also contains a full gene set for oxidative phosphorylation with oxygen as terminal electron acceptor and for reverse electron transport from nitrite to NADH. A novel variation of complex I may catalyze the required reverse electron flow to low-potential ferredoxin. Interestingly, comparative genomics indicated a strong evolutionary link between Nitrospina, the nitrite-oxidizing genus Nitrospira, and anaerobic ammonium oxidizers, apparently including the horizontal transfer of a periplasmically oriented nitrite oxidoreductase and other key genes for nitrite oxidation at an early evolutionary stage. Further, detailed phylogenetic analyses using concatenated marker genes provided evidence that Nitrospina forms a novel bacterial phylum, for which we propose the name Nitrospinae.